A Simulation of Rule-Breaking Behavior in Public Places. (August 2014) - Deguchi, Takuhiko
A computer simulation based on both game theory and the cellular automaton model was conducted to investigate the effects of individuals' interactions and certain conditions on the spread of rule-breaking behavior in public places. Four decision matrices representing obedient, deviant, conforming, and contrary principles were prepared experimentally. The ratio of these principles ranged from 1:2:3:4 to 4:3:2:1 (obedient:deviant:conforming:contrary). There were a total of 24 data sets with each data set composed of 10 decision matrices. In addition to these 24 data sets, the ratio 1:1:1:1 was prepared. This data set was composed of four decision matrices. The results indicated that rule-breaking behavior spreads under the following conditions: (A) when people act according to both individual factors (e.g., their attitudes) and situational factors (e.g., their neighbors' behavior); (B) when there are more deviant people than obedient people; (C) when the intensity of rule-breaking behavior is higher than that of rule-obeying behavior. Condition A is an important factor. If conditions B or C are satisfied, the spread of rule-breaking behavior does not occur necessarily. At a certain probability threshold, rule-breaking behavior spreads sharply when people act based on individual factors (e.g., their attitudes); the spread of such behavior cannot be attributed solely to situational factors (e.g., neighbors' behavior). There is only a fine line between rule breaking and obeying near the probability threshold.